Allograft function and muscle mass evolution after kidney transplantation. Issue 6 (15th September 2022) - Gaillard, François; Ould Rabah, Mélissa; Garcelon, Nicolas; Touam, Malik; Neuraz, Antoine; Legendre, Christophe; Anglicheau, Dany; Prié, Dominique; Bienaimé, Frank
Abstract: Background: Advanced chronic kidney disease is associated with muscle wasting, but how glomerular filtration rate (GFR) recovery after kidney transplantation is associated with muscle mass is unknown. Methods: We took advantage of the simultaneous measurement of GFR (using iohexol plasma clearance; ioGFR) and creatinine excretion rate (a surrogate marker of muscle mass; CER) performed 3 months after transplantation and at a later time point at our institution to investigate the interplay between allograft function, muscle mass, and outcome in kidney transplant recipients. Results: Between June 2005 and October 2019, 1319 successive kidney transplant recipients (mean age 50.4 ± 14.6; 38.7% female) underwent GFR measurement at our institution 3 months after kidney transplantation. CER (CER3 ) and ioGFR (ioGFR3 ) were 7.7 ± 2.6 μmol/min and 53 ± 17.1 mL/min/1.73 m 2, respectively. Multivariable analysis identified female gender, older donor and recipient age, reduced body mass index, coronary disease, dialysis history, proteinuria, and reduced ioGFR3 as independent predictors of low CER3 (ioGFR3 : β coefficient 0.19 [95% confidence interval 0.14 to 0.24]). A total of 1165 patients had a subsequent CER measurement after a median follow‐up of 9.5 months. Of them, 373 (32%) experienced an increase in CER > 10%, while 222 (19%) showed a CER decrease of more than 10%. Multivariable analysis adjusted for CER3 and other confounders identified ioGFR3 as an independent predictor of CER at follow‐up ( β coefficient 0.11 [95% confidence interval 0.07 to 0.16]). In multivariable Cox analysis, reduced CER at 3 months or at follow‐up were consistently associated with mortality (hazard ratio [95% confidence interval] at 3 months: 0.82 [0.74 to 0.91]; at follow‐up: 0.79 [0.69 to 0.99]) but not with graft loss. Conclusions: Glomerular filtration rate recovery is a determinant of muscle mass variation after kidney transplantation. Early interventions targeting muscle mass gain may be beneficial for kidney transplant recipients.